Peran Pendidikan Islam Dalam Membangun Karakter Religius Peserta Didik - Mahardika, Hendra; Santoso, Dimas Urip (Jayapangus Press, 2025)
Developments in this era of disruption show a rather worrying phenomenon in the morals of students. The proliferation of unscreened information means that students are easily exposed to negative content that can weaken their religious character, as well as the erosion of moral values in their daily interactions. In this case, Islamic education is important for shaping religious awareness and noble character. This study aims to analyze the role of Islamic education in building the religious character of students. Using a qualitative approach with a library research method, data was collected through searching various literature sources such as books, scientific articles, journals, and digital documents relevant to the research topic, then analyzed using content analysis techniques. The results of the study show that Islamic education shapes religious character through the interaction of internal factors, such as family, personality, teacher role models, and intentions, as well as external factors, including the school environment, peers, society, and digital culture. Islamic education is implemented through contextual PAI learning, religious-based extracurricular activities, worship habits, and school management that instills Islamic values. With this integrated strategy, students are not only ritually obedient, but also have noble character, spiritual awareness, social responsibility, and the ability to practice Islamic values in their daily lives. Thus, Islamic education becomes an ethical, moral, and spiritual foundation that is relevant in shaping a generation of character in the modern era.